Modeling as a Means to Develop New Ideas: The Case of Reinventing a Bifurcation Diagram. Issue 6 (3rd July 2019) - Rasmussen, Chris; Dunmyre, Justin; Fortune, Nicholas; Keene, Karen
Abstract: This article provides an overview of a modeling sequence that culminates in student reinvention of a bifurcation diagram. The sequence is the result of years of classroom-based research and curriculum development grounded in the instructional design theory of Realistic Mathematics Education. The sequence of modeling tasks and examples of student work tendered offers a fresh perspective on modeling and how an inquiry-oriented sequence of tasks can lead to the reinvention of significant mathematics.